On-Surface Isomerization of Indigo within 1D Coordination Polymers - Xu, Hongxiang; Chakraborty, Ritam; Adak, Abhishek Kumar; Das, Arpan; Yang, Biao; Meier, Dennis; Riss, Alexander; Reichert, Joachim; Narasimhan, Shobhana; Barth, Johannes V.; Papageorgiou, Anthoula C. (Angewandte Chemie - International Edition, 2024)
Natural products are attractive components to tailor environmentally friendly advanced new materials. We present surface-confined metallosupramolecular engineering of coordination polymers using natural dyes as molecular building blocks: indigo and the related Tyrian purple. Both building blocks yield identical, well-defined coordination polymers composed of (1 dehydroindigo : 1 Fe) repeat units on two different silver single crystal surfaces. These polymers are characterized atomically by submolecular resolution scanning tunnelling microscopy, bond-resolving atomic force microscopy and X-ray photoelectron spectroscopy. On Ag(100) and on Ag(111), the trans configuration of dehydroindigo results in N,O-chelation in the polymer chains. On the more inert Ag(111) surface, the molecules additionally undergo thermally induced isomerization from the trans to the cis configuration and afford N,N- plus O,O-chelation. Density functional theory calculations confirm that the coordination polymers of the cis-isomers on Ag(111) and of the trans-isomers on Ag(100) are energetically favoured. Our results demonstrate post-synthetic linker isomerization in interfacial metal-organic nanosystems.
Keywords: Coordination polymers; Indigo; isomerization; Noncontact Atomic Force Microscopy; scanning tunneling microscopy